Simple quantitative analysis of ascorbic acid in vitamin c related products using high performance liquid chromatography / Mahirah Mat, Siti Raihan Zakaria and Wan Siti Atikah Wan Omar - Mat, Mahirah; Zakaria, Siti Raihan; Wan Omar, Wan Siti Atikah (2014)
Antioxidant has gained interest among consumers regarding its significances in daily life. In this research, quantitative analysis of ascorbic acid in two samples of vitamin C related products by High Performance Liquid Chromatography (HPLC) had been studied. A reversed phase HPLC system with stationary phase of Phenomenex C18 column (250 x 4.6 mm) was used for the separation at ambient temperature with isocratic mobile phase of 0.1% phosphoric acid. The system was analyzed at the flow rate of 0.5 ml min-I and detection of dual-wavelengths ultraviolet; 245 nm and 270 nm, respectively. Successful separation of ascorbic acid of both samples had been achieved and the peaks resolved completely at retention time between 8 minutes until 10 minutes. The concentration of ascorbic acid for both samples also similar to the label on the bottles, 20 000 mg I-1. The stability test also had been done by keeping the samples in four different storage conditions. The results showed that concentration of ascorbic acid were stable for both samples after being exposed for six hours. The optimized method was further validated according to The International Conference on the Harmonization of the Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) as the standard guidelines. The method showed good system suitability, linearity (R2 > 0.99), recovery (> 20%), precision (%RSD) and sensitivity (limit of detection (LOD) and limit of quantification (LOQ)), indicating that the proposed method could be used for further quantitative analysis of ascorbic acid in vitamin C related products.